HIV, Cocaine Use, and Hepatitis C Virus: A Triad of Nontraditional Risk Factors for Subclinical Cardiovascular Disease. Issue 10 (October 2016) - Lucas, Gregory M.; Atta, Mohamed G.; Fine, Derek M.; McFall, Allison M.; Estrella, Michelle M.; Zook, Katie; Stein, James H.
Abstract : Objective—: We assessed cross-sectional and longitudinal associations of 3 nontraditional cardiovascular disease risk factors—HIV, cocaine use, and chronic hepatitis C virus infection—with 3 validated markers of subclinical cardiovascular disease: carotid artery plaque, albuminuria, and aortic pulse wave velocity in a well-characterized cohort. Approach and Results—: We measured carotid plaque at baseline and after 24 months, urine albumin/creatinine ratio every 6 months, and pulse wave velocity annually for up to 36 months in a predominantly black cohort of 292 participants (100 HIV negative and 192 HIV positive). Thirty-nine percent had chronic hepatitis C virus infection and 20%, 28%, and 52% were never, past, and current cocaine users, respectively. Sixteen percent, 47%, and 64% of those with none, 1 or 2, or all 3 nontraditional risk factors had ≥2 abnormal cardiovascular disease risk markers ( P =0.001). In fully adjusted models that included all 3 nontraditional risk factors, HIV infection was independently associated with carotid plaque progression (increase in the number of anatomic segments with plaque), albuminuria (albumin–creatinine ratio >30 mg/g), albuminuria progression (doubling of albumin–creatinine ratio from baseline to a value >30 mg/g), and pulse wave velocity. Cocaine use was associated with an ≈3-fold higher odds of carotid plaque at baseline, and hepatitis C virus infection was significantly associated with a higher risk of carotid plaque progression. Conclusions—: These results suggest that HIV infection, cocaine use, and hepatitis C virus infection are important nontraditional risk factors for cardiovascular disease and highlight the need to understand the distinct and overlapping mechanisms of the associations. Abstract : Supplemental Digital Content is available in the text.